Bibliometric Research Trends on Globalization and Socio-Cultural Issues in Elementary Education - Helga Merilla Zafirah Widad; Aulia Damayanti; Eko Handoyo; Indriana Eko Armaidi (Journal of Literature Review, 2026)
Globalization has influenced elementary education by bringing socio-cultural issues such as cultural diversity, multicultural education, global citizenship, empathy, collaboration, and cultural identity into classroom practices. This study aims to analyze research trends on globalization and socio-cultural issues in elementary education using a bibliometric approach. The data were obtained from the Scopus database using selected keywords related to globalization, global citizenship, cultural diversity, multicultural education, and elementary education. After applying filters based on publication year, subject area, document type, and language, 223 Scopus-indexed articles published between 2022 and 2026 were analyzed. Data analysis was conducted using the Scopus Analyze feature and VOSviewer software. The findings show that publications increased notably from 2024 to 2025. Indonesia and Spain were the most productive countries, while Social Sciences became the dominant subject area. Keyword co-occurrence analysis identified several major themes, including globalization in primary education, multicultural education and culture, and global citizenship education with character-related values. The overlay and density visualizations indicate that recent research trends have moved toward global citizenship education, empathy, collaboration, gender, textbooks, and educator roles. This study provides an overview of research development and future directions related to globalization and socio-cultural issues in elementary education.